KARAKALPAK AND UZBEK LANGUAGES PARALLEL CORPUS AND ITS SYNTACTIC ADAPTATION - Khudoyberganova Munisa Shonazar qizi (Western European Studies, 2025)
This article examines the creation and syntactic adaptation of a parallel corpus for Karakalpak and Uzbek languages. It describes the role of parallel corpora in Natural Language Processing (NLP), machine translation, and linguistic research. The study focuses on the PARATRANSLATOR platform, which integrates multilingual corpora and enables contextual translations. It analyzes morphological and syntactic tagging, alignment techniques, and structural correspondences between the two languages. Similarities and differences in grammar, phonology, and lexicon between Karakalpak and Uzbek are highlighted. The research emphasizes the importance of such resources for preserving low-resource languages and improving AI-based translation technologies.
Keywords: Parallel corpus; NLP; Machine translation